CHILD & LABOUR SCENARIO IN ODISHA - Nanda, Samir Kumar (@rquivo Brasileiro de Educação, 2019)
Based upon research in the state of Odisha in India, this article describes the labour scenario in the state of Odisha during the last 82 years. Odisha became separate state on 1st April 1936. Eighty-two years since the momentous day, much has changed in the Labour relation, Juveniles, Child Labour problem & Migrant Workers of Odisha. This article also explains the magnitude of child labour and steps taken by the Government to eliminate child labour, formation of Labour Union, status of migrant workers and bonded labour in the state of Odisha. Here an effort has been made to analyse the status of child labours as well as other labours in Odisha. Identification of the area of concentration of child labour & evaluations of dimensions of the problem has been made.